What is the Intelligent Tissue Theory and How Does it Relate to Acupuncture? - Fletcher Kovich (MEDrang Inc., 2020)
The intelligent tissue theory states that organ information is conveyed on electromagnetic waves and these are interpreted by bodily tissue, so that real-time organ states are reflected in the tissue at each organ's related meridian. This article describes the practical implications of this, how this relates to acupuncture, and how it accounts for the common acupuncture-related phenomena. The Chinese medicine notion of "chi" is also explored. Its history is described, including the 1970's reinterpretation. This article suggests that both the Nei Jing and also the 1970's model of how acupuncture works are merely metaphorical; do not describe reality; and that "chi" (which is central to these models) does not really exist. Alternative explanations are provided for all the common phenomena that are usually attributed to "chi", and a simple account of how acupuncture works is given.